Menghadapi Era Baru : Strategi Perbankan Dalam Menghadapi Perubahan Pasar Dan Teknologi Di Indonesia - Ferozi Ramdana Irsyad; Filja Azkiah Siregar; Jonatan Marbun; Hasyim Hasyim (Universitas 17 Agustus 1945 Semarang, 2024)
This research focuses on banking strategies in facing the new era in Indonesia, taking into account the rapid market and technological changes. This transformation is triggered by the development of financial technology (fintech) and the digital revolution, which aims to expand financial inclusion by providing easier and more flexible access for people. To remain competitive, banks need to continue to innovate and improve services to meet higher customer expectations. This research uses a qualitative approach with a literature review method to gain an in-depth understanding of banking strategies in the face of market and technological changes in Indonesia. Secondary data was collected from relevant scientific articles, journals and books, then analyzed descriptively and interpretatively. This analysis aims to identify common patterns, trends, and important findings related to product and service innovation strategies, as well as risk and compliance management in the banking industry in Indonesia. The results show that human resource capacity building, digital infrastructure investment, financial education and literacy, effective risk management, collaboration with regulators, adoption of the latest technology, and development of innovative products and services are crucial steps for banks in Indonesia to face dynamic market challenges. The implementation of these suggestions will help banks in Indonesia to be better prepared for change and provide the best services for customers.